Ethnobotanical study on some Malaysian anti-malarial plants: a community based survey - Al-Adhroey, A.H.; Nor, Z.M.; Al-Mekhlafi, H.M.; Mahmud, R. (2010)
Ethnopharmacological relevance: Various plants species are used in the traditional medicine for the treatment of malaria. This is the first community based ethnobotanical study in Peninsular Malaysia. Aim of the study: To investigate the plants traditionally used in the treatment of malaria in Malaysia. Materials and methods: An ethnobotanical survey was carried out among 233 Aboriginal and rural households, and traditional healers in malaria endemic areas in Peninsular Malaysia. Data were collected using a pre-tested questionnaire. Results: Nineteen species belonging to 17 families were identified. Twelve plant species have not previously been documented for the treatment of malaria in Malaysia. Conclusions: Findings of this study can be used as an ethnopharmacological basis for selecting plants for further anti-malarial phytochemical and pharmaceutical studies. (C) 2010 Elsevier Ireland Ltd. All rights reserved.